Occupational health and safety implementation and employee job satisfaction: A systematic review - Rhomadhoni, Muslikha Nourma; Yudhastuti, Ririh; Paskarini, Indriati; Ratriwardhani, Ratna Ayu; Ayu, Friska (Edelweiss Applied Science and Technology, 2025)
This study aims to examine the effect of Occupational Health and Safety (OHS) implementation on employee job satisfaction through a systematic literature review approach. Information was collected by searching for scientific articles from the ScienceDirect and PubMed databases, which were filtered based on relevance to the research topic. This study employed a literature review research methodology. The results indicated that OHS implementation has a positive and significant effect on employee job satisfaction. A safe work environment increases comfort, reduces stress, and encourages employee loyalty to the company. Additionally, other factors such as compensation, relationships among coworkers, and organizational culture also play important roles in strengthening the effect of OHS on job satisfaction. The conclusion of this study confirms that optimal OHS implementation is a vital strategy for creating sustainable job satisfaction and supporting the achievement of overall organizational goals. Effective implementation of Occupational Safety and Health (OHS) policies can enhance employee safety and comfort, which in turn promotes increased work productivity. Employees who perceive their work environment as safe and feel that their welfare is cared for tend to be more loyal and exhibit lower absenteeism rates. This directly impacts the company’s operational efficiency.